2023
DOI: 10.3390/min13050604
|View full text |Cite
|
Sign up to set email alerts
|

Coherence of Bangui Magnetic Anomaly with Topographic and Gravity Contrasts across Central African Republic

Abstract: The interactions between the geophysical processes and geodynamics of the lithosphere play a crucial role in the geologic structure of the Earth’s crust. The Bangui magnetic anomaly is a notable feature in the lithospheric structure of the Central African Republic (CAR) resulting from a complex tectonic evolution. This study reports on the coherence in the geophysical data and magnetic anomaly field analysed from a series of maps. The data used here include raster grids on free-air altimetric gravity, magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Magnetic models in the Bangui area indicated that either metamorphic rocks, BIFs or both rock types could be the sources of the BMA. Recently Lemenkova and Debeir (2023) shows good correspondence between the spatial distribution of greenstone belts, metamorphosed basalt, granites and the BMA in the Central part of the Central African Republic.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Magnetic models in the Bangui area indicated that either metamorphic rocks, BIFs or both rock types could be the sources of the BMA. Recently Lemenkova and Debeir (2023) shows good correspondence between the spatial distribution of greenstone belts, metamorphosed basalt, granites and the BMA in the Central part of the Central African Republic.…”
Section: Discussionmentioning
confidence: 87%
“…In the centre of the Central African Republic, these series constitute the Oubangui basin, interpreted as a synclinorium comprising several sub-basins (Boukeke, 1994). Thus, the BMA would be superimposed on the Oubangui basin, which is also marked by a large negative gravity anomaly of about − 80 mGals (Lemenkova and Debeir, 2023). The hypothesis on the source of the anomaly deduced by Regan and Marsh (1982) was made taking into account the superposition of the two anomalies on the Oubangui basin.…”
Section: Limitation Of Known Models Over the Bma Area And Speculationsmentioning
confidence: 99%